A Review of CAM for Procedural Pain in Infancy: Part I. Sucrose and Non-Nutritive Sucking. Issue 4 (2008) - Tsao, Jennie C. I.; Evans, Subhadra; Meldrum, Marcia; Altman, Tamara; Zeltzer, Lonnie K.
Abstract : There is increasing concern regarding the number of painful medical procedures that infants must undergo and the potential risks of alleviating infant pain with conventional pharmacologic agents. This article is Part I of a two-part series that aims to provide an overview of the literature on complementary and alternative (CAM) approaches for pain and distress related to medical procedures among infants up to six weeks of age. The focus of this article is a review of the empirical literature on sucrose with or without non-nutritive sucking (NNS) for procedural pain in infancy. Computerized databases were searched for relevant studies including prior reviews and primary trials. The most robust evidence was found for the analgesic effects of sucrose with or without NNS on minor procedural pain in healthy full-term infants. Despite some methodological weaknesses, the literature to date supports the use of sucrose, NNS and other sweetened solutions for the management of procedural pain in infancy.